Adjuvant tyrosine kinase inhibitor therapy improves outcome for children and adolescents with acute lymphoblastic leukaemia who have an ABL‐class fusion. (14th September 2020) - Moorman, Anthony V.; Schwab, Claire; Winterman, Emily; Hancock, Jerry; Castleton, Anna; Cummins, Michelle; Gibson, Brenda; Goulden, Nick; Kearns, Pam; James, Beki; Kirkwood, Amy A.; Lancaster, Donna; et al.
Abstract: Patients with an ABL‐class fusion have a high risk of relapse on standard chemotherapy but are sensitive to tyrosine kinase inhibitors (TKI). In UKALL2011, we screened patients with post‐induction MRD ≥1% and positive patients (12%) received adjuvant TKI. As the intervention started during UKALL2011, not all eligible patients were screened prospectively. Retrospective screening of eligible patients allowed the outcome of equivalent ABL‐class patients who did and did not receive a TKI in first remission to be compared. ABL‐class patients who received a TKI in first remission had a reduced risk of relapse/refractory disease: 0% vs. 63% at four years ( P = 0·009).